Frequency of Arrest of the Young, Chronic, Serious Offender Using Two Male Cohorts Paroled by the California Youth Authority, 1981-1982 and 1986-1987 - Linster, Richard L. ([Verlag nicht ermittelbar], 1999)
This study investigated the ways in which active offenders and their behavior patterns are related to individual characteristics. Data were collected to explore topics such as the nature of individual offending behavior, including offense mix and specialization, the frequency of offending, and the characterization of offender types. To address these issues, the post-release arrest patterns of two cohorts of male youths paroled by the California Youth Authority in 1981-1982 and 1986-1987 were examined. The project focused on modeling the frequency of recidivism and the correlates of arrest frequency. The frequency of arrest was measured during two periods: the first year following release and years two and three following release. Criminal justice variables in this collection provide information on county-level crime and clearance rates for violent and property crimes known to the police. Measures of parolees' criminal history include length of incarceration prior to current commitment, frequency of arrest, age at first arrest, and calculated criminal history scores. Personal and family characteristics include previous violent behavior, alcohol and drug abuse, family violence, neglect or abuse, degree of parental supervision, parental criminality, education, and school disciplinary problems. Demographic variables include age and race of the subjects.